Isotope Study of Groundwater in Arid Areas of Jaisalmer - Singh, D; Singh, Y P; Bairwa, S P; Dass, P; Porwal, C P; Mathur, K M (Annals of Arid Zone, 2016)
In order to understand the ground water recharge process in Shahgarh area of arid Jaisalmer district, an environmental isotopic study based on measurement of D, 180 and 3H contents was carried out on shallow groundwaters. The area is characterized by very low rainfall, sandy terrain and very little vegetation. Water level in the scattered shallow wells and hand pumps varies from 10 to 30 m. Stable isotope analysis of the water samples indicate very high depletion of the heavy isotope contents. i.e &D- -50%0 and &185 180.6 to -7% and suggest quite old origin of these waters. The 3H contents are also very low. A 3H tracer injection experiment at Mehrana indicated negligible recharge due to modern precipitation. The ground water is potable to brackish. the TDS ranging from 200 to 1500 mg/l. A higher fluoride content was observed in two wells.